Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Apotek Fathurrahman Di Kayuagung - Imam Suroso; Muhammad Deni; Aras Tulip; Vivin Afini; Arubina Bangsawan (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
This study aims to: find out how the quality of drug service to consumers at Faturrahman Pharmacy and find out how consumer satisfaction in receiving drug services at Faturrahman Pharmacy.The research method used in this study is associative (influence), namely this study is to determine the Effect of Service Quality on Customer Satisfaction of Fathurrahman Pharmacy in Kayuagung.Data analysis uses product moment correlation analysis and uses the R formula with the data collection method through questionnaires. The subject of this study was a consumer of Fathurrahman Pharmacy and a sample of 96 respondents was determined. Based on the calculation results using the product moment coefficient formula, the value of r = 0.9993 while the r table for n = 94 (96-2) with an error level of 5% or 0.05 is 0.2006. So, r count is greater than r table (0.9993>0.2006), this means that there is a positive and significant influence between service quality on customer satisfaction of Fathurrahman Pharmacy.Judging from the calculation, the value of the coefficient of determination is 99.86%. This means that the influence of personnel management information systems on employee performance is 99.86% and the remaining 0.14% is influenced by other factors. The results showed that Service Quality (X) has a correlation and affects Fathurrahman Pharmacy Consumer Satisfaction.